Effect of Dietary Olive Leaf Integration on Qualitative Characteristics of Sheep Cheese During Ripening - Michela Contò; Simona Rinaldi; Giacomo Contò; Daniele Sagrafoli; Carlo Boselli; Giuseppina Giacinti; Sebastiana Failla (Dairy)
Olive leaf by-products may be an important feed source for ruminants in the Mediterranean area, due to their nutritional value and high levels of functional metabolites. Additionally, their use can enhance the environmental and economic sustainability of the productions. To evaluate the effect of olive leaf supplementation on the fatty acid profile of sheep cheese, two farms with Comisana breed sheep with free access to pasture and fedwith 300 g/head/day of concentrate were considered. One farm supplemented the feed with clover hay ad libitum (NOL) and the other farm replaced hay with olive leaves (OLI) in the autumn period. Cheese analyses were performed at 15, 30, and 60 days of ripening. Saturated fatty acids were lower in OLI cheese than NOL cheese, while MUFA and PUFA n-3 and n-6 were higher in OLI cheese. Myristic acid (C14:0) and palmitic acid (C16:0) were lower in OLI cheese compared to NOL (8.31% vs. 8.90% and 21.52% vs. 24.95%, respectively), while oleic acid (C18:1 cis-9) was higher in OLI cheese (20.66% vs. 18.78%). Also, CLA cis-9 trans-11 (0.98% vs. 0.84%), and other isomers were higher in OLI cheese. Health indexes, such as the thrombogenic and atherogenic index, were lower in OLI than in NOL cheese (1.96 vs. 2.38 and 1.69 vs. 2.05, respectively) showing the improvement in the health quality of cheese due to olive leaf integration in directly on farm sheep feeding.